Determinants of Share Price of Nepalese Commercial Banks - Bhattarai, Yuga Raj (Economic Journal of Development Issues, 2016)
This study examines the determinants of share price of commercial banks listed on the Nepal Stock Exchange Limited over the period of 2006 to 2014. Data were sourced from the annual reports of the sampled banks and analyzed using regression model. The results revealed that earning per share and price- earnings ratios have the significant positive association with share price while dividend yield showed the significant inverse association with share price. The major conclusion of the study is that dividend yield, earning per share and price-earnings ratio are the most influencing factors in determining share price in Nepalese commercial banks. Economic Journal of Development Issues Vol. 17 & 18 No. 1-2 (2014) Combined Issue,Page: 187-198